Cognitive functioning among poor elderly persons: Evidence from Peru - Rafael Novella; Javier Olivera (IZA Journal of Development and Migration, 2017)
The recent emergence and expansion of non-contributory pension programmes across low- and middle-income countries responds and contributes to a larger attention towards the population of elderly individuals in developing countries. These programmes are intended to reduce poverty in old age by providing monetary transfers in mean-tested schemes. However, little is known about the most salient characteristics of this population, particularly health outcomes and their relationship with socioeconomic demographics. The aim of this paper is to provide evidence about this relationship in the specific case of cognitive functioning. We exploit the baseline sample of the Peru's non-contributory pension programme Pension 65 and find significant relationships between cognitive functioning and retirement, education, nutrition, ethnicity and sex.
Keywords: J14; J24; 330; Cognitive functioning; Old-age poverty; Peru